169k views
5 votes
Solve for p. 2(p+ 5) = 16

Solve for t. -3(t + 1) = 18

Solve for x -2/5 (x+10)=-10

Solve for x. 2/3 (x -10)=-2

User Polynomial
by
5.5k points

2 Answers

1 vote

Hello!

The answers are:

1
p=3

2
x=-7

3
x=35

4
x=7

Why?

To know the solution of the problems, we need to isolate each variable.

Remember that:

- If we have an equality: if the number is part of a product , and if you need to move it to the other side of the equality, the same number will be dividing the factors of the side.

- If we have an equality: if the number is subtracting (negative sign), and if you need to move it to the other side of the equality, its sign changes to positive.

- If we have an equality: if the number is adding (positive sign), and if you need to move it to the other side of the equality, its sign changes to negative.

- The distributive property states that:


a(b+c)=ab+ac

So,

1 - Solving for p


2(p+5)=16\\2p+10=16\\2p=16-10=6\\p=(6)/(2)=3

2 - Solving for t


-3(t+1)=18\\-3t-3=18\\-3t=18+3=21\\t=(21)/(-3)=-7

3 - Solving for x


-(2)/(5)(x-10)=-10\\-(2)/(5)x+(2)/(5) *10=-10\\-(2)/(5)x+4=-10 \\-(2)/(5)x=-10-4=-14\\-(2)/(5)x=-14\\x=(-14)/((-2)/(5) )=14*(5)/(2)=35

4 - Solving for x


(2)/(3)(x-10)=-2\\\\x-10=(-2)/((2)/(3) )=-2*(\\3)/(2)\\\\x-10=-3\\x=-3+10\\x=7

Have a nice day!

User OffensivelyBad
by
5.2k points
4 votes

Answer:

1)
p=3

2)
t=-7

3)
x=15

4)
x=7

Explanation:

1) Apply distributive property:


2(p+ 5) = 16\\2p+10=16

Subtract 10 from both sides of the equation and then divide both sides by 2:


2p+10-10=16-10\\(2p)/(2)=(6)/(2)\\p=3

2) Apply distributive property:


-3(t + 1) = 18\\-3t -3= 18

Add 3 to both sides of the equation and then divide both sides by -3:


-3t -3+3= 18+3\\(-3t)/(-3)=(21)/(-3)\\t=-7

3) Apply distributive property:


-(2)/(5)(x+10)=-10\\\\-(2)/(5)x-4=-10

Add 4 to both sides of the equation:


-(2)/(5)x-4+4=-10+4\\\\-(2)/(5)x=-6

Multiply both sides by
-(5)/(2):


(-(2)/(5)x)(-(5)/(2)) =-6(-(5)/(2))\\\\x=15

4) Apply distributive property:


(2)/(3)(x-10)=-2\\\\(2)/(3)x-(20)/(3)=-2

Add
(20)/(3) to both sides of the equation:


(2)/(3)x-(20)/(3)+(20)/(3)=-2+(20)/(3)\\\\(2)/(3)x=(14)/(3)

Multiply both sides by
(3)/(2):


((2)/(3)x)((3)/(2))=((14)/(3))((3)/(2))\\\\x=7

User Mario The Spoon
by
5.3k points